Analysis of Retaining Wall Calculation Using Manual Method and Plaxis Software on the Kuningan (Cipasung) – Majalengka (Cikijing) National Road Boundary Section STA.51+850 - Rudiansyah, Rudi; Sidqi, Taufiq; Kusumah, Nur Hadi; Rezeki, Ingrid Multi (Indonesian Journal of Advanced Research, 2025)
Landslide disasters are one of the risks that greatly threaten road stability, so proper handling is needed to solve the problem of landslides on national roads. The purpose of this study is to analyze the calculation of soil retaining walls using the manual method and Plaxis Software, in order to obtain a soil retaining wall that is safe to use, namely by calculating the stability of the soil retaining wall and the safety factors of the soil retaining wall. In addition, in the preparation of this study, data is needed to be used as material for processing analysis data such as soil data, dpt dimension data, spt data, rainfall data, drill log data, earthquake data The results of the analysis of manual calculations on the stability of type 1 and type 2 soil retaining walls show that the results are safe while the safety factor value  from the Software Plaxis analysis shows safe results.